2008
DOI: 10.14714/cp60.231
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Map Interface Usability: Learning from the Lakeshore Nature Preserve Interactive Map

Abstract: These are exciting days for cartography, as emerging technologies have greatly expanded the possibilities of online, interactive maps. These developments, however, now require cartographers to think about issues that only a few years ago fell solely in the domains of human-computer interaction (HCI) and web design. Further, given how fast these changes have occurred, there are few tried-and-true guidelines for building digital maps. This paper reports on the design, development, and evaluation of the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…That is users "simply" place a pushpin on a map and describe what they have encountered, or their concern, in a text box. This appears straightforward, but Nivala et al (2008), Roth and Harrower (2008), and Newman et al (2010) found that some users of web maps had difficulty navigating the map and did not understand, or misunderstood map symbols. This makes us question if a purely map-based approach is useful.…”
Section: Research Needs For Participatory Planning Platformsmentioning
confidence: 99%
“…That is users "simply" place a pushpin on a map and describe what they have encountered, or their concern, in a text box. This appears straightforward, but Nivala et al (2008), Roth and Harrower (2008), and Newman et al (2010) found that some users of web maps had difficulty navigating the map and did not understand, or misunderstood map symbols. This makes us question if a purely map-based approach is useful.…”
Section: Research Needs For Participatory Planning Platformsmentioning
confidence: 99%
“…Flexible map browsing (i.e. panning and zooming) is supported in the Map Panel (Roth & Harrower, 2008), allowing the user to zoom to a site of interest through direct manipulation of the map itself (e.g. double-click) and through a zoom slider widget.…”
Section: User-centered Design and Development Of Weevil Viewermentioning
confidence: 99%
“…The map view provides the cartographic interaction operators typical of a 'slippy' web mapping service (i.e., pan, zoom, overlay, retrieve) through the direct manipulation interface style (Roth, 2011). The analyst can manipulate the basemap in accordance with Google Maps mashup conventions, which include flexible map browsing (i.e., panning and zooming; Roth & Harrower, 2008) and toggling among multiple basemap depictions (e.g., overlay of a vector map, satellite image, shaded relief with land cover types). Selection of an individual proportional symbol plotted in the map view activates a popup window containing summary information (i.e., information retrieval), as well as updates the records list.…”
Section: Interactive Map Designmentioning
confidence: 99%